Галузі у яких використовуються 3d - Удовиченко, К. О. (ХНУРЕ, 2024)
3D-tekhnologії are widely used in the modern world in various fields, in cluding cinema, games, medicine, industry, education and advertising. They change the perception of reality and expand opportunities in many industries. In cinema, they are used to create impressive visual effects, in games - to create realistic immersive worlds. In medicine, they help create detailed organ models for training and surgery planning. In industry, they are used for rapid prototyping and optimization of production processes. In the field of education, they con tribute to the creation of interactive educational materials. For these purposes, various software products are used, such as AutoCAD, Blender, SolidWorks and many others.
Keywords: 3D-tekhnologії